2010
DOI: 10.1001/jama.2010.1065
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exposure to Violence and Potential Traumatic Events With Self-reported Physical and Mental Health Status in the Central African Republic

Abstract: Context For decades, the Central African Republic (CAR) has experienced violence, economic stagnation, and institutional failure. The latest wave of violence erupted in 2001 and continues to this day in some areas. Yet there has been little attention to the conflict and even less research to document and quantify the conflict's human cost. Objective To study levels of violence in CAR, including mortality levels, and the association between exposure to violence and traumatic events with self-reported physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Langhaug et al, 54 Vinck and Pham, 55 Elbedour et al 56 Higher probability: high rates of violence, unrest and disease mean probability of mortal threat is high in these environments Higher probability: prevalence of physical danger is higher for such women…”
Section: Implications For Therapymentioning
confidence: 99%
“…Langhaug et al, 54 Vinck and Pham, 55 Elbedour et al 56 Higher probability: high rates of violence, unrest and disease mean probability of mortal threat is high in these environments Higher probability: prevalence of physical danger is higher for such women…”
Section: Implications For Therapymentioning
confidence: 99%
“…The measure has been adapted and translated for use in conflict settings in Asia [1113], the Middle East [14], Africa [15, 16], and the former Yugoslavia [17, 18]. The HSCL-25 is currently available in a wide range of languages including Arabic [19], Hmong [20], Kiswahili [16], Pashto [14], Farsi, Dari, Bosnian, Somali [9], Vietnamese [21], Swedish [22], Serbo-Croatian, Russian [23], Tibetan [13], Indochinese [24, 25], and Khmer.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, other studies focusing on the HSCL in high-income, Anglophone countries have found support for a tripartite factorial model [28, 29] including (in addition to anxiety and depression) a mixed domain of symptoms, variously labelled as “general/mixed distress”, “autonomic anxiety”, and “somatic depression.” Nevertheless, greatest consistency has been found in the association between potentially traumatic events (PTEs) and ongoing adversities typical of post-conflict populations, with the HSCL-25 anxiety and depression scales, respectively, with some minor differences in these relationships between the two symptom domains [9, 15, 30, 31]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies show an increase in the incidence and prevalence of PTSD, anxiety, and depression among civilian populations as a consequence of war [4-7]. Given the high stress environments and low-resource settings in which they operate, medics are at particular risk for developing such mental health disorders [8].…”
Section: Introductionmentioning
confidence: 99%